Addressing Environmental Challenges through Artificial Intelligence (AI)-Powered Natural Disaster Management - Singh, Vijay; Agnihotri, Aastha (International Journal of Applied and Scientific Research, 2024)
Recent advancements in AI offer promising tools for enhancing disaster management which is crucial given the increasing frequency of climate-related disasters. The study aims to evaluate how AI technologies can be utilized to improve disaster preparedness, response, and recovery efforts, thus aiding in environmental resilience and sustainability. This paper examines the intersection of artificial intelligence (AI) and environmental sustainability, with a focus on the role of AI in managing natural disasters. By reviewing secondary data and existing research, the paper explores various AI applications such as predictive modeling, real-time monitoring, and decision support systems. The analysis reveals that AI can significantly enhance early warning systems, optimize the allocation of resources, and ensure timely interventions during emergencies. The findings highlight the importance of integrating AI technologies into disaster management strategies to foster environmental sustainability amidst growing climate-related risks. The paper also discusses the challenges and ethical considerations of implementing AI in this field and underscores the need for interdisciplinary collaboration and stakeholder engagement for successful implementation.